Effective teaching strategies and inclusive education practices: A case study in Andalucia - Fernández Batanero, José Maria (Education Policy Analysis Archives, 2010)
This paper shows the results obtained regarding the educational practices carried out at a high school, catalogued as a center of preferential educational intervention by the Andalusian Educational Administration. The focus of attention is on the students at risk of scholar exclusion, and therefore of dropping out. The methodological design for the investigation, of descriptive nature, has been that of a case study, with three sources of information: documentary analysis, classroom observations, and the perceptions of the persons in charge of implementing the attention to diversity measures. Among the conclusions from the study about prevention of early dropouts, it is worth mentioning, on the one hand, the importance of carrying out planning, organization and teaching strategies with regard to scholar inclusion. On the other hand, the necessity of bringing out new types of coexistence based on respect, as well as developing educational policies that help to encourage a higher level of social commitment, and a better professional development for teachers.